2012
DOI: 10.1517/17425255.2012.701618
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of zolmitriptan for the treatment of migraines

Abstract: Zolmitriptan has been considered effective treatment in the acute phase of migraine, menstrual-related migraine and cluster headache attacks. Pharmacokinetic parameters may vary as a consequence of gender differences, inter- and intra-subjects variability and delivery system. Zolmitriptan was developed with the aim of obtaining a lipophilic compound in order to be more rapidly absorbed and centrally active. Pharmacologically, pharmacokinetic parameters are responsible for its wide efficacy and the limited adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Absorption was substantially faster than for orally administered zolmitriptan, with less measurable N-desmethyl zolmitriptan metabolite, presumably due to a lack of first pass metabolism. PK parameters for subcutaneous sumatriptan and oral zolmitritpan in this study were similar to those previously reported [14,15].…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Absorption was substantially faster than for orally administered zolmitriptan, with less measurable N-desmethyl zolmitriptan metabolite, presumably due to a lack of first pass metabolism. PK parameters for subcutaneous sumatriptan and oral zolmitritpan in this study were similar to those previously reported [14,15].…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Firstly, triptans attenuated the release of vasoactive peptides trigeminal system, as well as reduced the migraine vascular inflammation. Moreover, triptans were shown to potentially inhibit the nociceptive pathway of central sensitization, thus helped to relieve the pain from migraine [103, 104]. …”
Section: Discussionmentioning
confidence: 99%
“…This implies that the efficacy of triptans in prevention of migraine depends on their concentrations. Considering that frovatriptan has a long half-life (26 h [33]) and zolmitriptan posses a short half-life (3 h [38]), the frequency and dose should be adjusted when a triptan is used in the prevention of MM.…”
Section: Discussionmentioning
confidence: 99%